Gravity-Driven Membrane Reactor for Decentralized Wastewater Treatment: Effect of Reactor Configuration and Cleaning Protocol - Ihtisham Ul Haq Shami; Bing Wu (Membranes, 2021)
In this study, three gravity-driven membrane (GDM) reactors with flat sheet membrane modules and various biocarriers (synthetic fibers, lava stones, and sands) were operated for municipal wastewater treatment. The effects of water head, periodically cleaning protocol, and operation temperature on the GDM reactor performance were illustrated in terms of membrane performance and water quality. The results indicated that: (1) the cake layer fouling was predominant (>~85%), regardless of reactor configuration and operation conditions; (2) under lower water head, variable water head benefited in achieving higher permeate fluxes due to effective relaxation of the compacted cake layers; (3) the short-term chemical cleaning (30–60 min per 3–4 days) improved membrane performance, especially when additional physical shear force was implemented; (4) the lower temperature had negligible effect on the GDM reactors packed with Icelandic lava stones and sands. Furthermore, the wastewater treatment costs of the three GDM reactors were estimated, ranging between 0.31 and 0.37 EUR/m3, which was greatly lower than that of conventional membrane bioreactors under lower population scenarios. This sheds light on the technical and economic feasibility of biocarrier-facilitated GDM systems for decentralized wastewater treatment in Iceland.